Utilizing Spotify as a Tool for Phonology Learning in English Language Education - Siregar, Hanny Sarah; Azmy, Nabila Putri; Nasution, Raja Farhan Ansory; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study investigates the potential of Spotify as a digital learning tool to support the development of phonological competence among students in English Language Education. As an increasingly popular platform among youth, Spotify offers not only musical content but also podcasts and speech-based audio materials that can be integrated into language learning strategies, particularly in phonology. Drawing from multiple previous studies, this research highlights that the use of Spotify especially through English songs with clear lyrics can enhance students’ pronunciation, listening comprehension, rhythm awareness, and their understanding of phonemes such as /?/, /?/, and /ð/, which are often difficult for EFL learners. Using a qualitative method involving student perceptions collected via questionnaires and focus group discussions, the study reveals that Spotify contributes to informal yet effective learning. Students report higher motivation and engagement due to the accessibility and emotional resonance of music-based learning. Unlike rigid textbook approaches, Spotify allows for repetitive, contextualized input that supports pronunciation mastery in a relaxed and personalized manner. In addition, the integration of digital tools like Spotify aligns with students’ daily habits, making phonological learning more practical and less intimidating. Although some studies show that Spotify may not always outperform traditional classroom instruction in terms of measurable pronunciation scores, its strength lies in improving learner autonomy, fostering a positive attitude toward language exposure, and making phonological learning more enjoyable. Therefore, Spotify is considered a promising supplementary resource for English phonology instruction in higher education settings.